Impak Penyebaran Berita Palsu melalui Media Sosial terhadap Masyarakat: Kajian Kes Mahasiswa Universiti Tun Hussein Onn Malaysia - Hamzah, Shahidah; Ani, Fauziah; Rameli, Norizan; Md Nor, Noranifitri; Halim, Harliana; Rahman, Riki; Mohd Ali, Adi Syahid; Attan, Nizam; Kamri, Khairol Anuar (Advances in Humanities and Contemporary Studies, 2020)
In today's era, social media is a technology that is not unfamiliar to every individual regardless of age, gender, and race. Statistics from the Malaysian Communications and Multimedia Commission (MCMC) show that as of December 2018, Malaysia has 28.7 million Internet users which are 87.4 percent of the total population of the country. This is because the world has been surrounded by scientific and technological advances that can have a great influence indirectly on modern human civilization and also have an impact whether positive or negative depending on the individual user. Therefore, there is no denying that one communication phenomenon in the Internet world that is increasingly popular at this time is social media. Facebook, Twitter, Instagram, Path, Pinterest to Google+ are increasingly universally and widely used. This study aims to identify public perceptions of the dissemination of news and information through social media on ethical construction among the community. A study design using a questionnaire through Google Form was conducted on 150 members of Universiti Tun Hussein Onn Malaysia, Pagoh Campus, which consists of students. The results of the study found that the construction of ethics is one of the most important elements of the dissemination of news and information through social media so that this medium is not abused by society from time to time.